Optimization of garlic (Allium sativum L.) vacuum drying process by response surface methodology (RSM) - Vakula Anita; Horecki-Tepić Aleksandra; Šumić Zdravko; Vidović Senka; Drinić Zorica; Pavlić Branimir (Journal on Processing and Energy in Agriculture, 2016)
The objective of this work was to optimize the vacuum drying of garlic in order to preserve good physical properties. Fresh garlic (Allium sativum L.) was dried by vacuum drying process under different drying conditions. Three level, three variable, Box-Behnken experimental design (BBD) with response surface methodology (RSM) was used for optimization of drying process in terms of physical properties (moisture content, water activity, total colour change and shear force). Heat surface temperature (48 - 78 °C), airpressure (30 - 330 mbar) and drying time (3 - 11 h) were investigated as independent variables. Experimental results were fitted to a second-order polynomial model, where multiple regression analysis and analysis of variance were used to determine fitness of the model and optimal conditions for investigated responses. Contour plots were generated from the mathematical model. The optimal conditions for vacuum drying and simultaneous optimization of all responses (physical properties of dried garlic) were heat surface temperature of 78 °C, airpressure of 30 mbar and drying time of 11 h. Chemical parameters (total phenols content and antioxidant activity) were investigated as significant quality indicators of dried garlic samples. Fresh garlic was also dried by lyophilization and conventional drying in order to compare quality of samples dried by different techniques. It could be concluded that vacuum drying results in dried products with good physical properties, which are similar to sample dried by lyophilization and significantly better than convective dried sample.